The effectiveness of Neuro-Linguistic Programming (NLP) on students’ motivation and attitude - Hj Md. Kamaruddin, Nafisah@Kamariah; Azman, Mohamad Lutfi Arash; Abdul Hamid, Ahmad Faqirudin (Penerbit UTHM, 2020)
Neuro-Linguistic Programming (NLP) was developed at the University of California at Santa Cruz in the 1970's by its founders and principal authors, Richard Bandler and John Grinder, a professor of linguistics (Tosey & Mathison, 2003). Richard Bandler was a mathematics and computer science students while John Grinder is a linguistics professor. NLP helps in the teaching and learning process, especially in the classroom management. NLP was first introduced in Malaysia in the 21st century and since there are many training centres such as Akademi NLP Malaysia which train Malaysian universities and polytechnic lecturers and NLP Malaysia Centre of Excellence (NLPMC) which was the first to train NLP in Malay language.